Functional Outcomes of Adults with Left Ventricular Assist Devices Receiving Inpatient Rehabilitation. Issue 2 (16th January 2013) - Nguyen, Elizabeth; Stein, Joel
Abstract : Objective: To study the functional outcomes of patients with left ventricular assist devices (LVAD) who were receiving inpatient rehabilitation. Design: This is a retrospective cohort study of adults with an implanted LVAD admitted to an acute inpatient rehabilitation unit (IRU) over a 14‐month period from March 2010 through May 2011. Setting: A tertiary care hospital. Patients: This study included 11 patients with an implanted LVAD who required acute inpatient rehabilitation. All the patients with LVADs were included irrespective of the initial admitting diagnosis. Nine patients were admitted for cardiac diagnoses and underwent LVAD placement before their transfer to the IRU; 2 patients received LVADs before this hospital admission and were admitted for stroke. Methods: Demographic, clinical, and functional data were abstracted. Acute care length of stay (LOS), IRU LOS, and discharge disposition, along with IRU Functional Independence Measure (FIM) scores, were analyzed. Main Outcome Measurements: The primary outcome measurements were IRU LOS, change in functional status (measured by the FIM), FIM efficiency (FIM gain/LOS), and discharge setting. Results: The mean ± standard deviation (SD) IRU LOS was 17.5 ± 8.9 days. The mean ± SD FIM gain was statistically significant at 28.6 ± 10.2 ( P < .0001), and compared favorably to benchmarks for mean FIM gains regionally (22.5) and nationally (23) for patients admitted to IRUs with a cardiac diagnosis. The mean (SD) FIM efficiency (FIM gain/IRU LOS) was 1.97 ± 1.1 compared with the regional mean of 2.27 and national mean of 2.28. Seven of the 11 patients were discharged directly home after inpatient rehabilitation, and 3 returned home after an additional acute hospital stay. One subject died after transfer back to the acute hospital service. Conclusions: The patients with LVADs in this study achieved clinically meaningful functional gains from inpatient rehabilitation that compared favorably with national benchmarks for patients with cardiac diagnoses. The majority of the subjects were successfully discharged home. IRUs should consider implementing rehabilitation programs for this growing patient population.